On Pythagorean Triples and the Primitive Roots Modulo a Prime - Jingzhe Wang (Journal of Mathematics)
In this paper, we use the elementary methods and the estimates for character sums to study a problem related to primitive roots and the Pythagorean triples and prove the following result: let p be an odd prime large enough. Then, there must exist three primitive roots x, y, and z modulo p such that x2+y2=z2.